Genomic and immune profiling of prognostic risk groups in IgM gammopathy reveals novel biomarkers beyond MYD88 L265P - David F. Moreno; David F. Moreno; Ferran Nadeu; Ferran Nadeu; Fara Brasó-Maristany; Fara Brasó-Maristany; Fara Brasó-Maristany; Sergi Vaqué; Sara Paz; Joan Mañé; Oriol Cardús; Elena Medina; et al. (Frontiers in Immunology)
BackgroundMYD88 L265P is an early mutation in IgM monoclonal gammopathy of undetermined significance (MGUS) and asymptomatic Waldenström macroglobulinemia (WM). Given the high prevalence of the MYD88 mutation observed in epidemiological studies, its presence is not sufficient to drive disease progression. In fact, a recent risk model of progression reported that the impact of other laboratory biomarkers was superior to the MYD88 mutation’s presence. Due to the low incidence of these clinicopathological entities, there is a need for a better characterization of tumor and immune cells that can help to identify novel biomarkers. We hypothesize that the characterization of the risk groups in asymptomatic patients could improve the discovery of drivers of disease progressionMethodsWe characterized the genomic and immune landscape of the most recent prognostic risk categories in 19 IgM MGUS and 17 asymptomatic WM patients. We performed targeted next generation sequencing (NGS) on CD19+ cells from bone marrow samples at diagnosis using a panel of 54 lymphoma-driver genes. Whole bone marrow samples were also used to measure mRNA gene expression in tumor and immune cells using the PanCancer ImmuneProfiling panel on the nCounter platform (NanoString).ResultsWe observed that low-risk patients were only characterized by the presence of MYD88 L265P, while intermediate- and high-risk groups harbored additional mutations on CXCR4, KMT2D, ARID1A and EP300. Regarding the mRNA expression analyses, we found an increased proportion of myeloid cells in the low-risk group, with monocytes having a significant decrease in low versus high-risk patients. The high-risk group also upregulated genes involved in the activation of NF-κB and B-cell receptor (BCR) signaling, while low-risk patients upregulated genes associated with an alternative activation of B cells or a decrease of the BCR signaling, such as TOLLIP, CEACAM1 and CR1.ConclusionsBeyond the MYD88 mutation, we described novel molecular mechanisms associated with high-risk patients, as an effort moving towards easy-to use new biomarkers in IgM gammopathy.